Comparison of ureteral stents removal by rigid cystoscope versus rigid ureteroscope: A prospective study - KC, Hari Bahadur; Acharya, Ganesh Bhakta (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Ureteral stents are regularly used after different urological procedures to keep the ureter patent. They are commonly removed by rigid cystoscope under local anesthesia, and patients often experience significant pain during and after stent removal. Due to its small caliber, a rigid ureteroscope may cause less pain and discomfort. The authors compared the pain scores during ureteral stent removal by rigid cystoscope and rigid ureteroscope. Methods: In this prospective comparative study, 105 patients undergoing ureteral stent removal under local anesthesia were randomly assigned to two groups. In group A (55 cases), the stent was removed by rigid cystoscope, while a rigid ureteroscope was used in group B (50 cases). The pain experienced during the procedure, at first void, and at 24 hours was noted using a visual analog scale (VAS) pain score (0 to 10). The lower urinary tract symptoms and other complications were also recorded.Results: The VAS pain score during the procedure and at first void was significantly higher in group A as compared to group B (3.65±1.9 vs 2.60±0.7, p